Development of a novel digital breath-activated inhaler: Initial particle size characterization and clinical testing. (December 2018) - Kesten, Steven; Israel, Elliot; Li, Guangxi; Mitchell, Jolyon; Wise, Robert; Stern, Tom
Abstract: Background: Delivery of inhaled respiratory medications have been associated with variable delivery of drug due to errors in device operations and have not been designed to monitor true delivery of medication. A fully digital breath-activated inhaled (DBAI) delivery platform has been developed with integrated firmware and software to address these limitations. Methods: the device was designed to produce similar aerosol particle output to a marketed albuterol MDI and to the albuterol/ipratropium combination in a soft mist inhaler (SMI). Cascade impactor studies were conducted to demonstrate comparable aerodynamic particle size distribution (APSD) metrics. Efficacy was evaluated by pharmacodynamic studies involving spirometry in two separate protocols with adult subjects having COPD (albuterol DBAI vs. albuterol MDI – Study A, albuterol/ipratropium DBAI single arm – Study B). Results: The total emitted doses (TED) were 81.9 ± 10.3, 109.3 ± 15.0 and 121.9 ± 7.0 μg/actuation for the DBAI, SMI and MDI respectively, and the fine (respirable) particle doses (FPD) were 56.2 ± 6.0, 61.7 ± 5.5 and 79.4 ± 2.7 μg/actuation. MMADs for albuterol sulfate were 1.93 ± 0.11, 1.75 ± 0.19, and 2.65 ± 0.05 μm for the DBAI, Respimat soft mist inhaler (SMI) and MDI respectively. The corresponding GSDs were 1.96 ± 0.16, 2.79 ± 0.25, and 1.48 ± 0.02 μm. The corresponding respirable fractions were 68.7 ± 3.2%, 57.3 ± 10.5%, and 65.2 ± 2.4%. Spirometric study A enrolled 23 subjects (age 64 ± 7.3 years, 39% male, FEV1 45 ± 14% predicted). Study B enrolled 23 subjects (age 65 ± 8.6 years, 43% male, FEV1 47 ± 10% predicted). For Study A, FEV1 at 20 min post-dose improved by 120 (167) mL (p = 0.002) for the DBAI device and 109 (183) mL (p = 0.008) for the MDI device (p = 0.86 for between group differences). For Study B, FEV1 (20 min post-dose) improved by 216 (126) mL (p < 0.001). Conclusion: The DBAI generated highly respirable aerosols containing albuterol sulfate that were similar to the MDI and SMI in respirable fraction but lower in dose. Subsequent pharmacodynamic studies delivering albuterol sulfate alone and in combination with ipratropium bromide confirmed similar responses for the DBAI compared with the other inhalers, which could possibly be related to a response ceiling. The DBAI breath-activated capability combined with the ability to monitor actual delivery of medication may improve effectiveness by overcoming patient miscoordination.